Effectiveness and Safety of Colistin in Multi Drug Resistant Urinary Tract Infections - Jismy Karakkattu, Anisha Mohan, Emmanuel James, Anil Kumar (Journal of Applied Pharmaceutical Science, 2017)
Colistin methanesulphonate is an inactive prodrug of which only 30% is converted to the active metabolite, colistin, in the blood and the remaining drug gets excreted unchanged in the urine. The active metabolite is eliminated through non-renal mechanisms. Hence its effectiveness in urinary tract infections (UTI) can be dubious due to the notion that no active metabolite is excreted into the bladder. But colistin has been used in clinical practice for various infections, including UTI, caused by multi drug resistant (MDR) bacteria and there is scarcity of specific reports on effectiveness of colistin in UTI. Hence the objective of our study was to evaluate the effectiveness and safety of colistin in UTI patients admitted to a tertiary care hospital. A prospective observational study was conducted on patients being treated with colistin for UTI. Safety of colistin was evaluated by assessing the causality of adverse dug reactions using Naranjo ADR probability scale and by the RIFLE criteria for severity of acute kidney injury. Clinical outcome was evaluated for each patient on completion of colistin therapy. A total of 80 patients received colistin therapy for UTI and 81% of the UTI were nosocomial. Fifty percent of UTI were relapses and urine cultures identified Klebsiella pneumoniae, Pseudomonas aeruginosa and Escherichia coli as the causative organisms, all of which were MDR. Though colistin dosages were adjusted as per creatinine clearance 36.3% of patients experienced nephrotoxicity. Clinical cure was obtained in 80% of UTI cases. Colistin is effective for treatment of UTI caused by MDR gram negative bacteria but colistin should be used judiciously due to its potential to cause nephrotoxicity.
Keywords: Effectiveness, colistin, MDR bacteria, nephrotoxicity, safety, UTI.